Ergogenic Properties of Caffeine in the Diet of Athletes - Fałczyńska, Aleksandra; Szkudlarek, Weronika; Woźniak, Kinga; Bieniek, Maciej; Dachowska, Sandra; Haraj, Jan; Sobkowiak, Marcin; Namysł, Maria; Matczak, Simon (Quality in Sport, 2026)
Caffeine is one of the most widely consumed and extensively studied ergogenic aids in both amateur and professional sports. Its prevalence spans athletes across a range of disciplines. While some athletes regard caffeine as beneficial for athletic performance, others incorporate it into their daily routine. In competitive sports, where every detail of preparation can be essential, caffeine supplementation is frequently employed to enhance physical performance, cognitive function, and training capacity. This review summarizes current scientific evidence regarding the pharmacokinetics, mechanisms, effects, and safety of caffeine use in athletic populations. Biochemically, caffeine is a naturally occurring methylxanthine with rapid absorption, high bioavailability, and predictable hepatic cytochrome P450 1A2 mediated metabolism. Its ergogenic effects are attributed to non-selective antagonism of central adenosine receptors, which increases nervous system excitability, reduces perception of effort and pain, and enhances neuromuscular, cognitive, and psychomotor functions. Evidence-based recommendations indicate that low to moderate doses of caffeine, administered before or during exercise, are effective for most athletes, while smaller repeated doses are advantageous during prolonged events requiring sustained performance. Caffeine is generally considered safe within recommended limits; however, individual variability in dietary habits, genetic factors, and sensitivity necessitates personalized supplementation strategies. Overall, caffeine is a safe and effective ergogenic aid when used appropriately, with optimal outcomes achieved through individualized protocols tailored to specific sports and competition contexts.